The Effect of Jajar Legowo Planting System on Growth and Production of Some Varieties Paddy (Oryza sativa L.) - LORENTA REBEKKA SIMAREMARE; JONATAN GINTING; HARYATI HARYATI (Jurnal Agroekoteknologi, 2018)
This study aims to determine the effect of legowo row planting system on the growth and production of several varieties of rice fields (Oryza sativa L.). This research was conducted in paddy field of Balai Benih Induk Padi Murni Tanjung Morawa Agriculture Agency of North Sumatra Province from November 2016 until March 2017. This research used Factorial Random Block Design with 2 Factors of Treatment. The first factor is the jajar legowo planting system consisting of 3 levels L0 = Control (10 x 25 cm), L1 = 2: 1 (10 x 25 cm), L2 = 4: 1 (10 x 25 cm) and the second factor is varieties with 4 levels V1 (Mekongga), V2 (Situ bagendit), V3 (Inpari 32), V4 (Inpari 30). The results showed that planting system of legowo 4 :1 had an effect on increasing productivity of paddy rice (Oryza sativa L.).     Keywords : jajar legowo planting system, rice, varieties.